Call for revisions to Computer Misuse Act. Issue 7 (July 2020) - Unknown
Abstract : A group of cyber security organisations, working under the banner of the CyberUp Campaign, are calling on the UK Government to revise the Computer Misuse Act (CMA), which they say is no longer fit for purpose.